Konsep Uang Dalam Perspektif Pemikiran Imam Al-Ghazali Serta Kontribusinya Terhadap Sistem Ekonomi Islam - Asri Sundari; Yadi Janwari; Dedah Jubaedah (Jurnal Iqtisaduna, 2022)
The function of money turns into multifunctional. The variety of money types are mainly as a medium of exchange for human needs. The broad understanding of money is something that can be generally accepted as a means of payment within a particular territory or as a means of paying debts and a tool for purchasing goods and services. The definition of money in the economic sense is a medium of exchange that can be accepted in general by the whole community and carry out the process of exchanging goods and services. In Islamic economics, etymologically money comes from the word al-naqdu-nuqud. The meaning is that there are several meanings, namely al-naqdu which means good from dirham, grasping dirham, and al-naqdu also means cash. The word nuqud is not found in the Qur'an and hadith because the Arabs generally do not use nuqud to indicate price. The function of money can determine human activities, money can meet the needs of life and facilitate social activities. Money can be seen in terms of laws, logic, and traditions that can be accepted as the value of gold and silver. The currency derived from the material of the two metals cannot be said to be a currency.